Comparison of visual acuity outcome and choroidal thickness variation of intravitreal ranibizumab injection for myopic choroidal neovascularization with or without dome-shaped macula - Xiao-Fang Yin; Zu-Ke Ye; Xiu-Juan Guo; Chen Liang; Min-Hui Wu; Yu-Ting Luo; Yan Lu (Photodiagnosis and Photodynamic Therapy)
Background: To investigate the visual acuity outcome and choroid thickness (CT) change after intravitreal ranibizumab in highly myopic eyes with or without dome-shaped macula (DSM) in Chinese patients. Methods: This retrospective, observative study included 80 treatment-naive eyes (80 patients), which received ranibizumab according to the 1+PRN protocol. The best corrective visual acuity (BCVA) and CT change were compared between eyes with or without DSM. Results: There was no significant difference between eyes with or without DSM in BCVA and central macular thickness (CMT). The recurrent rate was not different between the two groups during the first year of treatment. The CT was significantly thinner in eyes with DSM than in eyes without DSM before treatment (median 40.00um versus 71.00um), at 1 month after treatment (median 31.00um versus 65.50um), and in the last follow up (median, 32.00um versus 65.00um) (p = 0.0101). Axial length (AL) was longer in eyes with DSM than those without DSM (median, 29.17 mm versus 28.10 mm) before treatment, and in the last follow up (median, 29.44 mm versus 28.20 mm) (p = 0.0055). The CT was significantly correlated with AL (p < 0.0001). Conclusions: No difference was found in visual outcome between eyes with or without DSM. The visual acuity significantly improved at 1 month after ranibizumab injection and it was recovery sooner in extrafoveal choroidal neovascularization (CNV) group than in subfoveal CNV group. The CT was thinner in eyes with DSM, which was significantly correlated with AL.